2023
DOI: 10.1088/1361-6668/acdc5c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high-quality joints between Gd–Ba–Cu–O bulk superconductors

N Tutt,
J Congreve,
Y Shi
et al.

Abstract: This work reports a technique for fabricating superconducting joints between GdBCO-Ag bulk superconductors, using YBCO-Ag as an intermediate joining material. The ability to provide reliable joints between multiple bulk superconductors overcomes many of the challenges of fabricating large superconductors or machining hard and brittle bulk superconductors into practical shapes. We report on nine single grains of GdBCO-Ag which have been joined with a YBCO-Ag intermediate. Samples were cut and joined in a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One of the advantages, therefore, is that there is a greater difference between the peritectic temperatures of the bulk superconductor (1046 • C) and the joining intermediate material (989 • C) [11,40]. There is a larger temperature gap between the bulk superconductor and joining intermediate than was present when joining GdBCO-Ag with a YBCO-Ag intermediate and, in the GdBCO-Ag/YBCO-Ag joining study, the best relative trapped field achieved was only 59% of that of the original sample prior to cutting [41]. This temperature gap provides a much greater range of temperature over which YBCO-Ag will be above its peritectic temperature, whereas the peritectic temperature of EuBCO-Ag will not be exceeded.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of the advantages, therefore, is that there is a greater difference between the peritectic temperatures of the bulk superconductor (1046 • C) and the joining intermediate material (989 • C) [11,40]. There is a larger temperature gap between the bulk superconductor and joining intermediate than was present when joining GdBCO-Ag with a YBCO-Ag intermediate and, in the GdBCO-Ag/YBCO-Ag joining study, the best relative trapped field achieved was only 59% of that of the original sample prior to cutting [41]. This temperature gap provides a much greater range of temperature over which YBCO-Ag will be above its peritectic temperature, whereas the peritectic temperature of EuBCO-Ag will not be exceeded.…”
Section: Introductionmentioning
confidence: 88%
“…There is, however, a disadvantage to this in that a higher joining temperature may cause more degradation of the surrounding bulk, single grain material, which is unavoidably heated during the joining process. In the work to join GdBCO-Ag, it has been shown that the additional heating the sample experiences during the joining process contributes directly to the degradation of the critical current [41]. In addition, greater consideration must be given to the migration of silver during the joining process compared to the use of silver-free YBCO.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible, but less likely reason is the diffusion of silver to any gaps at the joint interface to form a non-superconducting intermediate layer. A final possibility is the degradation of the localised J c in the bulk material due to the multiple heating cycles, as discussed in [40].…”
Section: Sample Growth and Joiningmentioning
confidence: 99%